Jadīd Urdū afsānah - Šahzād Manẓar (Manẓar Pablīkešanz, 1982)
Der Band enthält 17 im Zeitraum 1969-1982 geschriebene Aufsätze
Includes bibliographical references
Keywords: Aufsatzsammlung; Short stories; Urdu; Pakistan; Criticism; interpretation; etc